Reverse engineering design of main rotor and tail rotor of 2 - seater helicopter [electronic resource] - 325787 Vun, Tze Tsin (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2007